Pharmacokinetics, Pharmacodynamics, and Safety of Landiolol Hydrochloride in Healthy Chinese Subjects - Wang, M.; Zhang, Q.; Hua, W.; Zhou, W.; Huang, M.; Wang, H. (Drug Research, 2014)
Landiolol is an ultra-short-acting β-blocker that appears to be more cardioselective and less toxic than esmolol. The main objective of this study was to investigate the pharmacokinetics, pharmacodynamics, and safety of landiolol hydrochloride in healthy Chinese volunteers.We set 2-dose regimen (L and H groups) [L (low): 0.125 mg/kg/min (1 min) loading→0.02 mg/kg/min (20 min) continuous, H (high): 0.25 mg/kg/min (1 min) loading→0.04 mg/kg/min (20 min) continuous]. 20 healthy subjects of either sex were allocated randomly to the L and H groups (n=10, and 10). Blood samples were collected over 1 h after continuous infusion and were determined using a validated liquid chromatography/mass spectrometry (LC/MS/MS) assay. The safety of landiolol hydrochloride was assessed by adverse events recording, 12-lead ECG findings, physical examination, laboratory testing, and vital signs.The main pharmacokinetic parameters of landiolol hydrochloride in healthy Chinese subjects were as follows: doses of 2 groups (L and H); Cmax of 400±110 and 731±246 ng/mL; C21min of 327±109 and 508±141 ng/mL; Tmax of 10.1±6.5 and 6.2±5.7 min; t1/2 of 4.7±1.6 and 6.5±1.7 min. Landiolol hydrochloride was safe. There were no adverse events in any subject. The heart rates and blood pressures of subjects administered landiolol hydrochloride decreased, but no clinically significant changes were observed.The concentration of landiolol hydrochloride rapidly reached steady state levels, and rapidly dissipated after completion of administration. Landiolol hydrochloride appears to have rapid onset and short action.
Keywords: landiolol hydrochloride; ultra short-acting β1-blocker; pharmacokinetics; pharmacodynamics; safety